Immune Checkpoint Gene Polymorphism (CTLA-4 and TIM-3) as Risky Factors of Brain Tumor (from Grade I to IV) Incidence in Iraqi Population - Al.Ammar, Saba Amer Mughir; Al.Alwany, Shakir H.Mohammed; AL.Khafaji, Noor Salman Kadhim (Iraqi Journal of Science, 2026)
Brain and central nervous system cancer was the fourth most common cause of death in Iraq. Brain tumors can hijack immune checkpoint gene polymorphisms to evade immune surveillance and promote tumor progression. T-cell immunoglobulin and mucin domain 3 (TIM3) are type I membrane proteins that are associated with tumor and immune cells regulation. The cytotoxic T-lymphocyte antigen-4 (CTLA-4) is an inhibitory cell surface receptor that can modulate T-cell proliferation. This study aimed to investigate the impact of TIM-3 and CTLA-4 genes polymorphism on brain tumor susceptibility in the Iraqi population. One hundred fifty tissue samples were taken from brains enrolled in current research, including 100 brain tumor patients and 50 brain tissues as control, which were taken directly from the deceased in accidents. The DNA was extracted, and the TIM-3 and CTLA-4 genes were amplified using PCR. Then, the TIM-3 and CTLA-4 gene polymorphisms were identified using the Sanger sequencing method. A significant difference was found among brain tumour patients according to sex and age group (P=0.04 and 0.004, respectively). A novel mutation in the TIM3 gene at intron 2 position 157106624 C>A was identified, a statistically significant increase in CA mutant genotype frequencies in patients compared to controls (P=<0.0001). Also, the A allele was significantly increased in the brain tumor patients (34%), P=0.001, OR=0.216(0.081-0.577). A mutation in CTLA4 gene at exon 4 rs60872763 DEL(AT) was first identified, and the frequencies of Del(AT)21 fragments were increased significantly in patients with a brain tumor (93.3%) P<0.001, OR=0.048(0.014-0.160). The A allele and AC heterozygote genotype in TIM3 gene at intron 2 position 157106624 and CTLA-4 rs60872763 Del(AT)21 repeats may play roles as risky factors in the pathogenesis of brain tumors in Iraqi patients.